2021
DOI: 10.7759/cureus.17869
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Hospitalizations in the USA: Proportion of Hospitalizations With Non-Alcoholic Fatty Liver Disease in Non-Obese Population

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD), one of the leading causes of end-stage liver disease, is known to be associated with obesity. However, only a few studies in the United States (US) have described non-obese NAFLD, most of which were on the outpatient population. AimWe aimed to investigate the proportion of hospitalizations in the US with a diagnosis code that included NAFLD in the non-obese population. MethodsWe analyzed adult discharges from the Nationwide Inpatient Sample with a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…6,21 In fact, a recent study investigated the hospitalization trends for those with lean/nonobese NAFLD compared to obese NAFLD using the US National Inpatient Sample database. 22 They determined that over the 5-year span of their study, the hospitalization rate increased yearly among the lean/nonobese as compared to the obese NAFLD population. The lean NAFLD population was also older and had fewer metabolic comorbidities but were more likely to have cirrhosis, decompensated cirrhosis, and die.…”
Section: Discussionmentioning
confidence: 99%
“…6,21 In fact, a recent study investigated the hospitalization trends for those with lean/nonobese NAFLD compared to obese NAFLD using the US National Inpatient Sample database. 22 They determined that over the 5-year span of their study, the hospitalization rate increased yearly among the lean/nonobese as compared to the obese NAFLD population. The lean NAFLD population was also older and had fewer metabolic comorbidities but were more likely to have cirrhosis, decompensated cirrhosis, and die.…”
Section: Discussionmentioning
confidence: 99%
“…23 Studies have found that despite the absence of obesity, non-obese NAFLD subjects had a higher risk of death. 24 Furthermore, patients with NAFLD have been found to be independently associated with an increased risk for diabetes in non-obese subjects. 25 We found that NAFLD was common in non-obese patients with schizophrenia.…”
mentioning
confidence: 99%